Determinants of the Thai Corporate Bond Liquidity - Yakean, Somkid (Indian Journal of Finance, 2013)
The Thai bond market has developed rapidly, but it is unbalanced between the Government bonds and corporate bond markets. The corporate bond market is still undeveloped. This study aims to study the determinants which influence the corporate bond market liquidity. The period of this study is from January 2005 to October 2012. Based on the results of multiple regression, this study finds that the spread between yield to maturity and market rate and exchange rate influence the corporate entities in issuing bonds. This study also investigates the relationship between the spread between yield to maturity and market rate and issued amount of corporate bonds. The result shows that there is a relationship between the spread between yield to maturity and market rate and issued amount of corporate bonds. We can conclude that the corporate entities depend on the spread between yield to maturity and market rate in order to raise funds from the market. This study suggests that less fluctuation of spread between yield to maturity and market rate and exchange rate can encourage the corporate entities to mobilize funds from the market. The concerned organizations in the Thai bond market should carefully control the factors that obstruct the market participants to participate in the market. Finally, the authorities of the Thai bond market should encourage the market participants to participate in the Thai corporate bond market.